NUCLEAR ENERGY IS THE ANSWER TO COPE WITH THE LACK OF ENERGY AND GLOBAL WARMING - Wisnu Arya Wardhana (BATAN, 2009)
NUCLEAR ENERGY IS THE ANSWER TO COPE WITH THE LACK OF ENERGY AND GLOBAL WARMING. This paper of nuclear energy is the answer to cope with the lack of energy and global warming based on the analysis of energy demand which is increasing rapidly, meanwhile the energy reserve is limited and decreased. Mostly world’s energy is generated by fossil fuel energy, mainly oil and coal. Fossil fuel energy and industrial activities produce green house gases (GHG) such as : COx, CH4, N2O, and CFC which cause of global warming. Global warming gives bad impact to environment and to human being. Every country in the world needs sufficient energy, but the energy resources is limited and decreased. The answer for this solution must be an energy source which doesn’t produce green house gases. Why nuclear energy is chosen to cope with the lack of energy and global warming will be explained briefly in this paper.